Are DXA/aBMD and QCT/FEA Stiffness and Strength Estimates Sensitive to Sex and Age? - Rezaei, Asghar; Giambini, Hugo; Rossman, Timothy; Carlson, Kent D.; Yaszemski, Michael J.; Lu, Lichun; Dragomir-Daescu, Dan (Annals of biomedical engineering, 2017)
Dual X-ray absorptiometry (DXA) measures areal bone mineral density (aBMD) by simplifying a complex 3D bone structure to a 2D projection and is not equally effective for explaining fracture strength in women and men. Unlike DXA, subject-specific quantitative computed tomography-based finite element analysis (QCT/FEA) estimates fracture strength using 3D bone mineral distribution and geometry. By using experimentally-measured femoral stiffness and strength from a one hundred sample cadaveric cohort that included variations in sex and age, we wanted to determine if QCT/FEA estimates were able to better predict the experimental variations than DXA/aBMD. For each femur, DXA/aBMD was assessed and a QCT/FEA model was developed to estimate femoral stiffness and strength. Then, the femur was mechanically tested to fracture in a sideways fall on the hip position to measure stiffness and strength. DXA/aBMD and QCT/FEA estimates were compared for their sensitivity to sex and age with multivariate statistical analyses. When comparing the measured data with DXA/aBMD predictions, both age and sex were significant ( p ≤ 0.0398) for both femoral stiffness and strength. However, QCT/FEA predictions of stiffness and strength showed sex was insignificant ( p ≥ 0.23). Age was still significant ( p ≤ 0.0072). These results indicate that QCT/FEA, unlike DXA/aBMD, accounted for bone differences due to sex.